2020
DOI: 10.33545/27080013.2020.v1.i2a.11
|View full text |Cite
|
Sign up to set email alerts
|

Population size and spatial distribution pattern of Schizaphis graminum (Hemiptera: Aphididae) on some wheat cultivars and lines

Abstract: Field experiments were conducted at wheat program of El-Mattana Agricultural Research Station, Luxor Governorate, Egypt during two successive growing seasons (2017/2018 and 2018/2019) to study the performance of some wheat cultivars and lines to infestation by Schizaphis graminum (Rondani) (Hemiptera: Aphididae) and their spatial distribution pattern. Results indicated that the total population density of S. graminum during the first growing season (2017/2018) was higher than second growing season (2018/2019)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…According to Green's model, it is recommended to place 2-3 delta traps with pheromone per hectare during periods of high population density and increasing the number of traps during periods when the population is typically low. The estimation of optimum sample size is fundamental for reducing the time required for monitoring pests (Bakry & Shakal, 2020;Ward et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Green's model, it is recommended to place 2-3 delta traps with pheromone per hectare during periods of high population density and increasing the number of traps during periods when the population is typically low. The estimation of optimum sample size is fundamental for reducing the time required for monitoring pests (Bakry & Shakal, 2020;Ward et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…According to Green's model, it is recommended to place 2–3 delta traps with pheromone per hectare during periods of high population density and increasing the number of traps during periods when the population is typically low. The estimation of optimum sample size is fundamental for reducing the time required for monitoring pests (Bakry & Shakal, 2020; Ward et al., 1985). Typically, the monitoring of P. citrella population involves the observation of larvae on young branches (Jahnke et al., 2008; Jesus & Redaelli, 2008; Liu et al., 2008; Tsagkarakis et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have concluded that hemipteran pests have a high aggregated distribution behavior. Example: Chauliops fallax (Hemiptera: Malcidae) on soybean (Bala and Kumar, 2018), Waxiella mimosae on sunt trees (Bakry, 2018), Parlatoria oleae on mango trees (Bakry, 2020), Aulacaspis tubercularis (Hemiptera: Diaspididae) on mango trees (Bakry and Abdel-Baky, 2020), Icerya seychellarum on guava trees (Bakry and Arbab, 2020), Schizaphis graminum (Hemiptera: Aphididae) (Bakry and Shakal, 2020), and Phenacoccus solenopsis on okra plants . The data presented in Table (4) and Figure (5) showed the toxicity activity of some insecticides against F. virgate after 72 hrs of treatment.…”
Section: Spatial Distributionmentioning
confidence: 99%
“…These models can be converted from probability distributions to frequency distributions by multiplying each probability by the size of the mealybugs sample. This provides several advantages, such as expressing the spatial dispersion of the mealybug population in mathematical terms, evaluating errors in population parameters, comparing spatial and temporal shifts in mealybugs population density, and estimating the impact of ecological factors (Bakry, 2020;Bakry & Abdel-Baky, 2020;Bakry & Shakal, 2020;.…”
Section: Introductionmentioning
confidence: 99%
“…Zeb et al (2011) tested the resistance of different varieties (Pirsabak-2004, pirsabak-2005, pirsabak-2008, KT2004, Khyber-81, PR1, R2, NRL0320, and Saleem-2000,they found that the susceptible variety PR1 recorded the highest average density for aphids, including S. graminum, with an average of 42.20 aphids.plant -1 , compared to the sensitive variety Pirsabak-2004, which recorded the lowest population density of aphids. Also, Bakry & Shakal (2020) stated that Giza-171 (susceptible variety) had the highest density of Greenbug, compared to variety Line 4 had the lowest density.…”
Section: Responses Of Local Wheat Varieties To Greenbug S Graminum and R Padi Infestationmentioning
confidence: 99%